Gestão ambiental : gerenciamento de resíduos de serviços de saúde em hospital veterinário universitário - Figueredo, Jucelia Farias de (2020)
This study intends to analyze the waste management of the University Veterinary Hospital of the Federal University of Sergipe while aiming to identify the reality of the practices developed by the institution’s professionals, as well as the introduction and/or adequacy of the correct practices in the management of Health Service facility Waste, Resíduos dos Serviços de Saúde (RSS). This waste regardless of its origin and classification needs to be properly managed as it can lead to human, animal and environmental contamination. To prevent possible risks and damage related to this wastes all kinds of healthcare facilities must adopt the Waste Management Plan of Healthcare facilities, Plano de Gerenciamento dos Resíduos dos Serviços de Saúde (PGRSS). It is a study with quantitative and qualitative approach characterized as a descriptive exploratory study. The search results prove that the PGRSS have not been adopted yet by the analyzed institution causing ignorance of the procedures and standards by the professionals with consequent mistakes in some steps of the management process of RSS. It is expected that this study might contribute to the introduction of the PGRSS in the analyzed institution leading to the proper management and disposal of solid waste and RSS. It is also intended to contribute to the academic formation and professional qualification of professionals aware of the development of proper waste management with consequent reduction of potential threats to healthcare workers, community and environment.